Knowledge, Attitude and Practices on Antimicrobial Resistance and Usage Among Medical Students in A Malaysian Medical University - Jaiprakash, Heethal; Patil, Ameeta; Kale, Sunil; Shidhaye, Pallavi R (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Abstract—Drug resistance is a fast mounting crisis. Many factors, like the inappropriate use of antimicrobials by prescribing physician, unregulated sale of drugs and self-medication, have been attributed to the increase in the incidence of antimicrobial resistance. Health care professionals are a significant determinant in this regard their in-depth knowledge is essential for rationale antimicrobial usage. The objective of this study is to analyze the knowledge, attitude, and practice of antimicrobial usage and resistance among different years of medical students. This is a cross-sectional questionnaire-based study that was conducted among yr. 1 to yr.5 students. A validated Questionnaire was obtained. The questionnaire assesses the students on their attitude, practice, and knowledge of antimicrobial resistance and usage. The data were analyzed using descriptive statistics. A total of 543 students participated in the study. Antimicrobial resistance was recognized as an essential and serious public health issue in today’s era by 92.16% Year 5 respondents, which was highest among all the years (Year 1-5). The awareness regarding the etiology of cold and flu was observed to be the highest among Year 4 respondents (65.74%). Only 2.8% of the total respondents strongly agreed that skipping one or two doses of antimicrobials does not lead to the development of resistance. 49.02% of the year five respondents always consulted a physician before starting an antimicrobial, indicating a good practice. However, when it came to checking the expiry date of antimicrobials before taking it, the Year 1 respondents (53.95%) were more particular. The study revealed that some aspects of knowledge regarding antimicrobial resistance and usage were found to be significantly higher among the respondents in the clinical years. The said knowledge was well-reflected in some, but not all of the facets of the respondent’s attitude and practice.